Pedagogical Practices and Creative Classroom Environments: Enhancing Language and Arts Achievement among Secondary School Students in Italy - Alessandro Ricci (Britain International of Linguistics Arts and Education (BIoLAE) Journal, 2015)
This study examines the influence of pedagogical practices and classroom environments on students’ achievement in language and arts education at the secondary school level in Italy. The research involved 92 secondary school students from an urban public school in Italy and employed a quasi-experimental design. A two-way ANOVA was conducted to evaluate the effects of interactive versus traditional teaching approaches and collaborative versus individualistic classroom settings on students’ performance in language and arts subjects. Achievement was measured through a combination of written assessments, creative projects, and oral presentations. The findings indicate significant main effects for teaching practices, with interactive approaches resulting in higher student performance compared to traditional instruction. Similarly, classroom environment demonstrated a significant effect, with collaborative settings promoting better outcomes than individualistic learning structures. The interaction effect between teaching practices and classroom environment was not statistically significant, suggesting that each factor independently contributes to student achievement. From a linguistic and artistic perspective, interactive and collaborative approaches were found to enhance students’ expressive abilities, critical thinking, and engagement with both language and creative tasks. These findings support educational frameworks that emphasize student-centered learning, creativity, and social interaction as key components of effective language and arts education. Future research should explore longitudinal impacts and include diverse school settings to strengthen generalizability.